Physics E-book with Augmented Reality to Improve Students’ Interest in Physics - Novita, Ria Riski (Jurnal Pendidikan Indonesia, 2023)
In the 21st century, science and technology are becoming important factors in education to support teachers and students in accessing learning resources easily. This study aims to develop physics e-books with augmented reality in PBL and to determine the effectiveness of e-book physics with augmented reality in PBL to increase student interest. The research method uses the type of Research and Development (R&D) research with 4D models, namely Define, Design, Develop, and Disseminate. The subjects of the limited product trial consisted of 30 students, while the subjects of the broad product trial consisted of 105 students. Sample selection technique using random sampling technique. The results showed that physics e-books with augmented reality on temperature and heat materials are very feasible to be used in learning based on assessments by experts in media and material aspects and are suitable for use based on student responses. The use of augmented reality-assisted physics e-books in learning shows that students' interest in learning physics in experimental classes is better than control class 1 and control 2. This shows that the use of interesting augmented reality-assisted physics e-books is able to attract interest in learning so that students are more active in learning.